Cover Image, Volume 66, Issue 7. Issue 7 (9th June 2017) - Di Bello, Maria Pia; Mergola, Lucia; Scorrano, Sonia; Del Sole, Roberta
Abstract : The cover image, by Maria Pia Di Bello et al., is based on the Research Article Towards a new strategy of a chitosan‐based molecularly imprinted membrane for removal of 4‐nitrophenol in real water samples, DOI:10.1002/pi.5360 . Abstract : The cover image, by Maria Pia Di Bello et al., is based on the Research Article Towards a new strategy of a chitosan‐based molecularly imprinted membrane for removal of 4‐nitrophenol in real water samples, DOI:10.1002/pi.5360 .